Antibacterial, Antifungal And Subchronic Toxicity Test Of Ficus Deltoidea Jack Leaves Extract - Apriasari, Maharani Laillyza; Adhiya, Geyanina Melda; Wasiaturrahmah, Yusrinie; Utami, Juliyatin Putri; Firdaus, I Wayan Arya Krishnawan; Pramitha, Selviana Rizky (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Ficus deltoidea Jack is a plant that is often used as herbs medicine because of secondary metabolites such as alkaloids, phenolics, flavonoids, and steroids. This study aims to determine the activity of antibacterial, antifungal and toxicity effect of Ficus deltoidea Jack leaves (FDLE) extract. Method: Pure experimental study with a posttest-only design with a control group design. The in vitro test by dilution methods using Staphylococcus aureus and Candida albicans. The toxicity test used 16 male Rattus novergicus divided into four group consist a control group and three treatment group given FDLE doses with 1,250, 2,500, and 3,750 mg/kgBW. The treatment applied 2x1 ml FDLE every 24 hours orally for 28 days. Result: The MIC value and the MBC value of FDLE againts S. aureus were 8% and 10%, respectively. While, MIC and MBC value on C. albicans has similar value about 25%. The mean results of kidney toxicity test were still in the normal range. There was a significant difference in the results of the Kruskall Wallis test for urea (p<0.05), while there was no significant difference in the results of urea and creatinine level (p>0.05). Conclusion: There was antibacterial and antifungal efficacy of FDLE. Also, there was no toxic effect of giving FDLE at doses of 1,250, 2,500, and 3,750 mg/kgBW was showed on urea and creatinine normal level.